Natural Killer Cell Protocols Cellular and Molecular Methods - Campbell, Kerry S.; Colonna, Marco; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2000)
In Natural Killer Cell Protocols: Cellular and Molecular Methods, Kerry S. Campbell and Marco Colonna have assembled a comprehensive collection of readily reproducible methods designed to study natural killer (NK) cells from the broadest variety of viewpoints. These include not only classic techniques, but also new approaches to standard methods, newly evolved techniques that have become valuable for specific applications, and unique models for manipulating and studying NK cells. Among the advanced methods covered are those for in vitro transendothelial migration, in vivo detection of cells migrating into tumors, immunofluorescence staining of intracellular cytokines, and in vitro NK cell development. Valuable techniques for specific applications include vaccinia virus protein expression, soluble KIR-Fc fusions for HLA class I binding assays, calcium mobilization in cell conjugates, and identification of heterodimeric receptor complexes using cDNA library expression cloning. No less important are accounts of such classic methods as hybrid resistance, ADCC, viral defense, target cell cytotoxicity assays, cloning and culturing, tumor immunotherapy, and generation of HLA class I transfected target cells. Natural Killer Cell Protocols: Cellular and Molecular Methods offers immunologists, cancer researchers, virologists, and cell biologists today's most comprehensive collection of both established and cutting-edge techniques, methods that will contribute significantly to advancing our understanding of this fascinating and critically important class of cells.
Cloning Human Natural Killer Cells -- Generation of Short-Term Murine Natural Killer Cell Clones to Analyze Ly49 Gene Expression -- Cloning and Culturing of Fetal Mouse Natural Killer Cells -- Techniques for Studying Development of Human Natural Killer Cells and T Cells -- Murine Natural Killer Cell Cloning from Fetal Thymic Organ Cultures -- Generation of HLA Class I Transfected Target Cell Lines -- Murine Natural Killer Cells and Hybrid Resistance to Hemopoietic Cells In Vivo -- Hybrid Resistance by Mouse NK Cells In Vitro -- Use of Activated Natural Killer Cells for Tumor Immunotherapy in Mouse and Human -- Methods for In Vivo Analyses of Natural Killer (NK) Cells -- Assay for theTransendothelial Migration of Human Natural Killer Cells -- Methods of Analyzing Chromatin Changes Accompanying Apoptosis of Target Cells in Killer Cell Assays -- Methods for Detecting Lytic Granules in Natural Killer Cells -- Fluorogenic Substrates as Detectors of Caspase Activity During Natural Killer Cell-Induced Apoptosis -- Techniques For Studying Murine Natural Killer Cells in Defense Against Viral Infection -- Assays for Antibody-Dependent Cell-Mediated Cytotoxicity (ADCC) and Reverse ADCC (Redirected Cytotoxicity) in Human Natural Killer Cells -- Multiple Color Immunofluorescence for Cytokine Detection at the Single Cell Level -- Generation of Antibodies to Cell Surface Markers on Mature Natural Killer Cells -- Human Single-Chain Fv Fragments Specific for Natural Killer Cell Receptors from Phage Display Libraries -- Binding of Soluble KIR-Fc Fusion Proteins to HLA Class I -- Genetic Analysis of a Highly Homologous Gene Family -- Use of Vaccinia Virus for Functional Gene Transfer in Natural Killer Cells -- Use of cDNA Library Expression Cloning to Identify Components of Heterodimeric Receptor Complexes -- Functional Analysis of Natural Killer Cell Receptors in the RNK-16 Rat Leukemic Cell Line -- Use of Mutant JurkatT Cell Lines to Define Human Natural Killer Cell Surface Receptor Signaling Pathways -- Measurement of Calcium Mobilization Responses in Killer Cell/Target Conjugates by FACS Analysis -- BIAcore Analysis to Test Phosphopeptide-SH2 Domain Interactions -- Analysis and Use of Mutant Mice Exhibiting Natural Killer Cell Defects -- Isolation and Analysis of Natural Killer Cells in Chickens -- Analyzing Nonspecific Cytotoxic Cells in Fish -- Natural Killer Cells and Immunotoxicology.
Keywords: Immunology; Immunology